Subjective perception of activity level: A prognostic factor for developing chronic dizziness after vestibular schwannoma resection? - Van Laer, Lien; Hallemans, Ann; Van Rompaey, Vincent; De Valck, Claudia; Van de Heyning, Paul; Vereeck, Luc (Frontiers in Neurology, 2022)
Introduction: A vestibular schwannoma (VS) resection causes an acute unilateral vestibular deafferentation resulting in acute postoperative symptoms. Despite the expected resolution of most of the symptoms, due to central vestibular compensation, more than one out of four patients develop chronic dizziness. Several predictive factors, such as age and tumor size, have been suggested. Despite its potential effect on the process of central vestibular compensation, the level of physical activity after VS resection was not yet considered. Therefore, the association between the level of physical activity and chronic dizziness after VS resection will be investigated. Methods: This retrospective case-control study included sixty-six patients who underwent a retro-sigmoid VS resection between October 2001 and February 2007. Patients were assessed prior to surgery and at 9 and 26 weeks postoperatively. At 9 weeks, patients were asked to report their level of physical activity (PA) during the past week by using a visual analogue scale and their balance performance was assessed by four standing balance conditions with eyes closed and the Timed Up and Go test (TUG). Based on the Dizziness Handicap Inventory (DHI)-score at six months, patients were divided in a chronic dizziness-group (DHI >30) and not-chronic dizziness group (DHI-score≤30). Age, sex, Koos-classification, preoperative vestibular function, treatment group, balance performance and level of PA were compared between both groups and used as independent variables in linear regression analyses with the DHI-score at six months as dependent variable. Results: The chronic dizzy patients revealed to have significantly lower levels of PA (p< 0.001) and worse static and dynamic balance performance (p= 0.023 and p= 0.041 respectively) 9 weeks after surgery. After elimination, the multiple regression analysis resulted in a model with two variables (PA level, TUG) which significantly predicted the DHI-score (F2,42= 6.581; R2= 0.239; p= 0.003). Conclusion: This study revealed associations between (1) the level of PA and balance performance in the subacute phase and (2) chronic dizziness after VS resection. Assessment of the level of PA and balance performance during the subacute phase, which can be performed in a non-invasive and non-time-consuming way, might therefore provide prognostic information after VS resection.